Mandated emergency care for sepsis: faster might not always be (much) better - Lather, Kanwar Sudhir; Kuan, Win Sen (Journal of Emergency and Critical Care Medicine; Vol 1 (August 2017): Journal of Emergency and Critical Care Medicine, 2017)
The concept of early goal-directed therapy (EGDT) was originally pioneered by the seminal work of Rivers and colleagues published in 2001. It was a single-center, randomized, controlled trial of EGDT versus usual care in patients presenting with septic shock to an urban emergency department in the United States (1). EGDT was defined as a 6-hour resuscitation protocol for the administration of intravenous fluids, vasopressors, inotropes, and transfusion of red cells to reach prespecified targets for mean arterial blood pressure, central venous pressure, central venous oxygen saturation, and hemoglobin level. In the original study, EGDT achieved 16% reduction in absolute risk of hospital mortality from 46.5% to 30.5%, thus prompting a worldwide rethink in the management of sepsis—emphasizing the need for aggressively seeking, recognizing, and treating severe sepsis. The era of EGDT had commenced.